Overview of the progress and prospects of SMAC mimetics in cancers: Is it a silver bullet? - Almuradova, Elvina; Malik, Durr-E-Shahwar; Yousaf, Sara; Ahmad Farooqi, Ammad (Archives of Pharmacy, 2022)
Loss of apoptosis results in the survival and uncontrolled proliferation of cancer cells. Basic and clinical researchers have dissected myriads of central regulators of apoptosis. Second mitochondria-derived activator of caspases (SMAC)/ direct inhibitor of apoptosis protein (IAP)-binding protein with low pI (DIABLO) has attracted phenomenal attention because of its amazing ability to trigger apoptotic death. Accordingly, different teams of interdisciplinary researchers are working on the design and development of SMAC mimetics which can significantly inhibit primary and secondary tumor growth.
Keywords: SMAC mimetics; cancer treatment; apoptosis; metastasis; tumor growth inhibition